2021
DOI: 10.1007/s11325-021-02527-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-access versus telemedicine home-based sleep apnea testing for obstructive sleep apnea (OSA) diagnosis: a cost-minimization study

Abstract: PurposeThe aim of the present study was to compare two clinical pathways: the multiple-access outpatient pathway versus the telemedicine pathway. Methods The multiple-access outpatient pathway and the telemedicine pathway were both performed with WatchPAT and implemented in a real-life healthcare scenario, adopting a cost-minimization approach. A cost-minimization analysis was undertaken to assess the economic impact of the two alternatives. The cost analyses were performed in euros for the year 2021 adopting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Home sleep studies (home sleep apnea testing or HSAT) offer a more accessible and convenient alternative to traditional in-lab sleep studies. Patients can conduct sleep studies in the comfort of their homes, which may increase overall participation in diagnostic assessments, especially among those who might find attending a sleep clinic challenging and expensive [42]. This advancement signifies a new potential avenue for expanding access to both diagnosis and treatment for OSA, addressing critical gaps in care exacerbated by the pandemic.…”
Section: Home Sleep Studies Driven By Technology Innovations and Arti...mentioning
confidence: 99%
“…Home sleep studies (home sleep apnea testing or HSAT) offer a more accessible and convenient alternative to traditional in-lab sleep studies. Patients can conduct sleep studies in the comfort of their homes, which may increase overall participation in diagnostic assessments, especially among those who might find attending a sleep clinic challenging and expensive [42]. This advancement signifies a new potential avenue for expanding access to both diagnosis and treatment for OSA, addressing critical gaps in care exacerbated by the pandemic.…”
Section: Home Sleep Studies Driven By Technology Innovations and Arti...mentioning
confidence: 99%
“…A cost-effectiveness study using an unspecified WP device found that the telemedicine pathway was more expensive for the healthcare provider but significantly cheaper for patients, indicating that a telemedicine service with WP devices would be acceptable to the patient population (Di Pumpo et al, 2022). Use of the WP device rather than full PSGs in traditional outpatient services has been shown to reduce time to OSA diagnosis and treatment, leading to overall cost savings (Phua et al, 2021).…”
Section: Diagnosis Of Osa By Watchpatmentioning
confidence: 99%
“…Although sleep testing can guide treatment, these tests pose meaningful access barriers and costs to patients and the healthcare system. In-laboratory testing is a particular concern because it requires substantial patient time and travel along with major investments from healthcare systems for dedicated facilities and staff ( 6 , 7 ). Although home sleep apnea testing can alleviate many of these barriers, home tests can still require staff time for study retrieval, scoring, and interpretation ( 7 ).…”
mentioning
confidence: 99%
“…In-laboratory testing is a particular concern because it requires substantial patient time and travel along with major investments from healthcare systems for dedicated facilities and staff ( 6 , 7 ). Although home sleep apnea testing can alleviate many of these barriers, home tests can still require staff time for study retrieval, scoring, and interpretation ( 7 ). Together, these barriers and costs limit the feasibility of follow-up sleep testing among patients treated with MADs.…”
mentioning
confidence: 99%
See 1 more Smart Citation